1976
DOI: 10.1007/bf01577621
|View full text |Cite
|
Sign up to set email alerts
|

A post-residential-treatment follow-up of socially and emotionally deviant adolescents in Israel

Abstract: Fifty-five emotionally and socially deviant but normally intelligent adolescents who had spent 2-7 years in a children's and apprentice home in Israel were followed up 5-9 years after they had left the institution. Their postresidential social and vocational careers were evaluated by means of personal interviews, home visits, and reports from employers, and it was found that good adjustment was substantially related to family background variables (having lived with biological parents prior to residential place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The critique was also fueled by the expense of long‐term residential care and the increasing number of children referred to these facilities. Furthermore, follow‐up research in Israel found no association between years in care and current functioning (Kohen‐Raz & Jonas, ; Schiff, Benbenishty, & Research Group: Mental Health and Well Being in Childhood and Adolescence, ; Weiner & Kupermintz, ). The social atmosphere and empirical evidence supported a shift toward collaborative family practices, which was back‐winded by parallel processes in other countries and by Israel's 1991 ratification of the United Nations Convention on the Rights of the Child ().…”
Section: Historical Ethical and Empirical Backgroundmentioning
confidence: 99%
“…The critique was also fueled by the expense of long‐term residential care and the increasing number of children referred to these facilities. Furthermore, follow‐up research in Israel found no association between years in care and current functioning (Kohen‐Raz & Jonas, ; Schiff, Benbenishty, & Research Group: Mental Health and Well Being in Childhood and Adolescence, ; Weiner & Kupermintz, ). The social atmosphere and empirical evidence supported a shift toward collaborative family practices, which was back‐winded by parallel processes in other countries and by Israel's 1991 ratification of the United Nations Convention on the Rights of the Child ().…”
Section: Historical Ethical and Empirical Backgroundmentioning
confidence: 99%